2019
DOI: 10.5296/jei.v5i2.15301
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Agility Performance and Cognitive Parameters of Female Basketball Players

Abstract: Objective: This study aims at investigating the relationship between agility performance and perception and decision-making mechanisms of female basketball players.Materials and Methods: A total of seventeen elite female basketball player playing in Second League in Turkey Basketball Federation participated in this study voluntarily. The mean age of the participants was 21.53±2.47 (years), the mean height was 175.67±5.36 (cm) and the mean body weight was 66.80±7.76 (kg). Agility performance of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Scanlan et al [88] also reported that cognitive measures (response time and decision-making time) have the foremost influence on nonplanned (i.e., reactive) agility performance in male basketball players. Gokhan et al [89] had a consistent result when they found a significant negative linear relationship (r = 0.842 and r = 0.827, p < 0.01) between the total time of the RA test and the result of the Speed and Distance Estimation Test. These findings suggest that for improving real agility performance, it is not enough to practice COD tasks.…”
Section: Change Of Direction (Cod) and Agility Testsmentioning
confidence: 76%
“…Scanlan et al [88] also reported that cognitive measures (response time and decision-making time) have the foremost influence on nonplanned (i.e., reactive) agility performance in male basketball players. Gokhan et al [89] had a consistent result when they found a significant negative linear relationship (r = 0.842 and r = 0.827, p < 0.01) between the total time of the RA test and the result of the Speed and Distance Estimation Test. These findings suggest that for improving real agility performance, it is not enough to practice COD tasks.…”
Section: Change Of Direction (Cod) and Agility Testsmentioning
confidence: 76%